Who is responsible for keeping children healthy? A qualitative exploration of the views of children aged 8–10 years old. Issue 5 (27th May 2019) - Goldthorpe, Joanna; Epton, Tracy; Keyworth, Chris; Calam, Rachel; Armitage, Christopher
Abstract : Objective: The issue of who is responsible for children's physical health is complex, with implications for targeting and developing strategies for health promotion and interventions to improve health. While there is evidence to suggest that children are able to construct notions of responsibility in relation to other areas of their lives, very little research has explored children's views of responsibility for their own health. The aim of this study was to explore children's views about who they feel is responsible for keeping them healthy. Design: Focus groups were used to gather qualitative data using a semistructured topic guide. Interpretative phenomenological analysis was used in an iterative, double hermeneutic approach to analyse the data. Setting: Focus groups took place in two UK primary schools in deprived inner city areas. Participants: 20 children aged 8–10 years took part in one of two focus groups (10 children in each group). Results: Three overarching themes were identified: (1) individual and collective responsibility, (2) marketing and conflict with taking responsibility, and (3) what people and organisations can do to help children to take responsibility. Children feel that they, parents, families, school staff, medical professionals, food producers, retail outlets, supermarkets, advertisers and the government are all responsible for their health and should thus demonstrate responsibility through their behaviours around children's health. Conclusions and implications: Children's views were consistent with constructs of responsibility as both a moral obligation and a set of behaviours, and with wider sociopolitical philosophies of individual and collective responsibility. These findings further support a focus on integrated, system-wide approaches to children's health.